White spot syndrome virus infection in cultured penaeus vannamei (boone) in Ecuador with emphasis on histopathology and ultrastructure - Rodríguez, Jenny (2003)
White spot syndrome virus infection in cultured Penaeus vannamei (Boone) in Ecuador with emphasis on histopathology and ultrastructure